Societal engagement from a cooperative perspective: An exploratory case study - ALLIOUA, Abdelmoula (Revue du contrôle, de la comptabilité et de l’audit, 2020)
The cooperative system, by its purpose, values and foundations, carries a large part of the principles and foundations on which the concept of Corporate Social Responsibility (CSR) is based. It is a key player in responsible practices and has major assets to ensure that current and future generations are able to transmit a high-quality economic, environmental and social heritage. The purpose of this article is to contribute to a better understanding of how this approach is constructed, and what are the specificities of evaluation, through an exploratory case study, (Copag of Taroudant). Our research is exploratory and is essentially part of the interpretative philosophical tradition, which led to the construction of our research object and our problematic. The results that emerged from this study indicate that the cooperative's commitment to a social responsibility approach is a continuation of the identity building of the organization and the consistency between displayed values and daily action.